2010
DOI: 10.1016/j.jesp.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Aversive racism and medical interactions with Black patients: A field study

Abstract: Medical interactions between Black patients and nonBlack physicians are usually less positive and productive than same-race interactions. We investigated the role that physician explicit and implicit biases play in shaping physician and patient reactions in racially discordant medical interactions. We hypothesized that whereas physicians' explicit bias would predict their own reactions, physicians' implicit bias, in combination with physician explicit (self-reported) bias, would predict patients' reactions. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
252
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(267 citation statements)
references
References 32 publications
14
252
1
Order By: Relevance
“…Several studies [15][16][17] found that clinician implicit bias was associated with worse clinical interactions with black patients. In our own work with the same clinicians and patient population studied here, 15 black patients reported less patient-centered treatment from clinicians who had higher levels of implicit bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [15][16][17] found that clinician implicit bias was associated with worse clinical interactions with black patients. In our own work with the same clinicians and patient population studied here, 15 black patients reported less patient-centered treatment from clinicians who had higher levels of implicit bias.…”
Section: Discussionmentioning
confidence: 99%
“…Greater implicit bias among clinicians, in turn, has been linked to less patient-centered interactions with black patients. [15][16][17] Evidence on the effects of clinician implicit bias on medical decisions in hypothetical scenarios has been mixed. 13,[18][19][20] The linkage between clinician implicit bias and more technical processes and outcomes of care has not been Electronic supplementary material The online version of this article (doi:10.1007/s11606-014-2795-z) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [52][53][54] have found associations between clinicians' implicit bias and worse clinical interactions with black patients. Most relevant to CVD is a study by Blair and colleagues 44 in which primary care providers' levels of implicit race bias predicted differences between black and white patients' reports of their clinicians' patient centeredness, with black patients reporting less patient centeredness for clinicians previously categorized as having higher levels of implicit racial bias.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…In addition, next iterations of this evaluation might include implicit measures of attitudinal shifts, given known biases of self-reported attitudes regarding sensitive social topics. 83 Finally, due to a dearth of scales assessing MHPs' (or any healthcare professionals') attitudes toward and beliefs about transgender individuals, we adapted scales originally designed to assess health professionals' attitudes and beliefs regarding lesbian, bisexual, and gay individuals. These original scales' focus was on sexual orientation rather than gender identity.…”
Section: Limitationsmentioning
confidence: 99%